STUDIES ON THE EFFECTS OF PLANT EXTRACT TEPHROSIA PURPUREA ON THE OVOTESTIS OF SLUG LAEVICAULIS ALTE (FERUSSAC) (MOLLUSCA : GASTROPODA) - MURUGAN, P.; CHANDRAN, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Two different concentrations such as 1% and 2% of plant extract of Tephrosia purpurga were injected into slug Leavicaulis alte for five alternate days. The slugs were sacrificed on the 10" day of the experiment. The normal histological features of the ovotestis were affected both in 1% and 2% treated slugs. But the effects were higher in 2% treated slugs than 1% level.